(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Flowable concrete or self-consolidating or self-compacting concrete (SCC) is a particularly flowable, non-segregating concrete which flows, plugs formwork, and captures the utmost congested rebars with none use of mechanical vibration. When used with admixtures to enhance the performance of concrete, it is called as self-compacting high performance concrete. An extant literature survey was taken up to understand the utilization of waste polyethene, fly ash and micro-silica in SCC to make it a SCHPC. It has been seen that very less amount of research work is available on use of waste polythene in conventional concrete as well as SCC. A few studies have reported positive results towards the mechanical properties i.e. compressive strength and flexural strength of concrete while no literature is available taking into account its initial cost and the durability aspects of such concrete.